A UNIQUE MANAGEMENT OF TRACHEAL STENOSIS - Haq, Anwar -ul-; Bukhari, Syed Muhammad Asad Shabbir; Umar, Aasim (Journal of Ayub Medical College Abbottabad, 2006)
Advances in medical technology have dramatically improved one's chances of survival in a number of significant medical illnesses. Failed treatment of acute trauma to trachea, complication of endotracheal intubation and tracheostomy tubes are the common causes of tracheal stenosis. Tracheal stenosis can be treated by LASER ablation, dilatation, endoscopic stenting1, T-Tube, segmental resection and reconstruction2. Repair of tracheal injuried ends with placing of a stent through open neck incision after acute tracheal injury in order to prevent tracheal stenosis in future was a unique experience.